2019
DOI: 10.1016/j.fertnstert.2019.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive endocrinologists are the gatekeepers for male infertility care in North America: results of a North American survey on the referral patterns and characteristics of men presenting to male infertility specialists for infertility investigations

Abstract: M.K.S. has nothing to disclose. J.F.S. has nothing to disclose. K.C.L. is a past president of Society for the Study of Male Reproduction and is on the board of directors. J.M.H. owns equity in the following start-up companies unrelated to the submitted work: Stream Dx, Nanonc, and Andro360. S.L. has nothing to disclose. E.D.G. has nothing to disclose. J.C.T. has nothing to disclose. T.J.W. has nothing to disclose. P.N.K. has nothing to disclose. V.D.W.C. has nothing to disclose. A.S.Z. is a shareholder of YAD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 8 publications
0
22
0
Order By: Relevance
“…As such, the inability to easily locate a reproductive urologist online constitutes a significant barrier to healthcare access. Recently, Samplaski et al (19) found that a very small but significant proportion (4.2%) of men seeing male fertility specialists were self-referred. This small number could be, in part, attributable to the difficulty of finding a male factor infertility specialist online.…”
Section: Discussionmentioning
confidence: 99%
“…As such, the inability to easily locate a reproductive urologist online constitutes a significant barrier to healthcare access. Recently, Samplaski et al (19) found that a very small but significant proportion (4.2%) of men seeing male fertility specialists were self-referred. This small number could be, in part, attributable to the difficulty of finding a male factor infertility specialist online.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the Male Reproductive Health Initiative (MRHI) has been organized to increase global awareness of male reproductive health and advocate to funding agencies the need for greater investment in research (39), and ReproUnion (https://reprounion.eu/) is organized to address big questions in reproductive medicine through international collaborations. Lastly, the Andrology Research Consortium (ARC) was founded to standardize data collection, clinical information and therapeutic approaches for the treatment of male infertility (40). As these and other efforts emerge and further mature, they will continue to accelerate the advancement of research in reproductive medicine.…”
Section: Collaborative Approachesmentioning
confidence: 99%
“…Male factors, alone or combined with female factors, explain up to 50% of infertility cases, and when present, an evaluation by a urologist experienced in diagnosing and treating male factor infertility is highly recommended. In Brazil, like the United States and Canada (1), most patients are referred to urologists by (reproductive) gynecologists based on an abnormal semen analysis result. The work-up involves a detailed medical history and physical examination and, when indicated, hormone, genetic, and imaging tests, all of which are used to guide clinical management (2).…”
Section: Introductionmentioning
confidence: 99%